Doświadczanie wdowieństwa a nowe związki romantyczne w okresie późnej dorosłości - Rodziejczak, Klaudia (Człowiek i Społeczeństwo, 2021)
The current population of widows and widowers in Poland is over 3.1 mln, whereof the vast majority is over 60 years old. Death of long-life partner is one of the most stressful events in an individual’s life and it may affect their physical and mental condition. At the same time acceptance of spouse’s death and successful adaptation to widowhood are the developmental tasks of late adulthood phase, which may provide to personal growth. A widowed person can decide if they desire to engage new romantic relationship. Research shows that starting a new relationship is motivated by various factors: psychological (e.g. spouse idealization, anxiety), biological (e.g. age, health), and external factors (e.g. socioeconomic situation). New late-life romantic relationships differ from previous stages of life – we can observe changes in: relationship goals, dynamic of the relationship and together activities, although seniors experience passionate love the same way that younger generations do.